Treatment Adherence and Incidence of Coronary Heart Disease in Type 2 Diabetes Mellitus Patients - Baniu, Ahmad Sahlan; Sauriasari, Rani; Riyadina, Woro; Soewondo, Pradana (Kesmas, 2022)
Previous studies showed that uncontrolled blood sugar and long-term use of several types of antidiabetic could increase the risk of coronary heart disease (CHD). This study aimed to compare the incidence of CHD in type 2 diabetes mellitus (T2DM) patients showing treatment adherence and non-adherence behavior over four years. This was a retrospective cohort study with data sets obtained from the Bogor Cohort Study of Non-Communicable Disease Risk Factors. All study subjects were not diagnosed with CHD at the beginning of the study. The sample was divided into two groups; one had adhered to treatment from health centers and followed the treatment instructions (adherent group), while the other had not followed the treatment instructions (non-adherent group). Of 5,690 subjects, 276 were eligible for this study (84 in the adherent and 192 in the non-adherent group). The incidence of CHD in the non-adherent group was 2.3% higher than in the adherent group (p-value = 0.564) and had a 1.7 times greater risk of developing CHD, but not statistically significant (adjusted HR = 1.739; 95% CI = 0.673-4.490). The non-adherent T2DM patients had a greater risk of developing CHD than adherent T2DM patients.